2009
DOI: 10.1001/archdermatol.2008.572
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Adrenal Insufficiency Following Systemic Glucocorticoid Therapy in Infants With Hemangiomas

Abstract: Setting: Hemangioma and vascular malformation center at a tertiary care children's hospital. Patients: Sixteen infants with hemangiomas had an adrenal axis evaluation as soon as possible following the completion of GC therapy. Ten healthy control infants were also evaluated for comparison. Interventions: Prednisolone at a starting dose of 2 to 3 mg/kg/d for 4 weeks, followed by a tapering period. The mean duration of GC treatment was 7.2 months. Main Outcome Measure: Prevalence of adrenal insufficiency in GC-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…7 Since the first report in 2008, 8 oral propranolol treatment for severe hemangioma has shown great advantages 9-11 with a trend of replacing oral corticosteroids. The clinical effect has been confirmed by numerous clinical studies.…”
Section: Discussionmentioning
confidence: 99%
“…7 Since the first report in 2008, 8 oral propranolol treatment for severe hemangioma has shown great advantages 9-11 with a trend of replacing oral corticosteroids. The clinical effect has been confirmed by numerous clinical studies.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, patients who have been treated with adalimumab, infliximab or etanercept for other autoimmune disorders have developed alopecia areata during the course of treatment 168,169 . Finally, small randomized trials of efalizumab (anti-CD11A) 170 and alefacept (anti-CD2) 171 showed no benefit in alopecia areata.…”
Section: Mechanisms/pathophysiologymentioning
confidence: 99%
“…The authors commented that measuring morning serum cortisol levels, which is less specific than corticotropin stimulation test for assessing the HPA axis suppression, and measuring the cortisol levels while the patient is still on corticosteroid therapy could explain the higher incidence of adrenal insufficiency reported in the earlier studies. [24]…”
Section: Introductionmentioning
confidence: 99%